Micro-erosion meter measurements, Roaring River, Mammoth Cave, Kentucky, USA - Bosch, Rachel; Ward, Dylan J; Bird, Aaron (University of Cincinnati, 2019)
This is an ongoing study measuring bedrock denudation of the limestone floor in the baselevel Roaring River passage in Mammoth Cave, Mammoth Cave National Park, Kentucky, USA. The project was initiated under USNPS research permit # MACA-2017-SCI-0019. Data includes location of micro-erosion meter stations relative to cartographic survey stations established by the Cave Research Foundation, depth micrometer measurements at those stations, and structure-from-motion photogrammetry data at those stations.
Keywords: abrasion; cave; Dissolution; erosion; Geomorphology; Karst; micro-erosion meter; scallop; sculpted bedrock